(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT The honorable Sunnah of the Prophet is considered the second source of legislation in Islam after the Book of God Almighty, as it explains and explains it. The Prophet - may God bless him and grant him peace - did not leave this world until he explained to the people what was revealed to them from their Lord and left them on the clear proof, and God Almighty prepared it. Men from this nation Among the people of knowledge and virtue, they preserved the Sunnah of the Prophet, wrote it down, explained it to the people, defended it, examined it, and removed from it what was alien to it, and so it is in every generation. Among these distinguished men is Ka’b bin Ujrah - may God be pleased with him - who is the imam, the great companion, Abu Muhammad, Ka’b Ibn Ujrah Ibn Amr Ibn Umayyah Al-Ansari, Al-Salmi, Al-Madani, Al-Sawadi - may God be pleased with him - died in the year fifty-two.For the migration, he studied at the hands of a large number of scholars and jurists, including: Omar Ibn Al-Khattab and Bilal Ibn Rabah - may God be pleased with them -, and a large number of them studied at his hands: Abdullah bin Omar and Abdullah bin Abbas - may God be pleased with them -, and as for the Imam Al-Darimi is: the Imam, the Hafiz, Abdullah bin Abdul Rahman Al-Darimi, Al-Samarqandi, died in the year two hundred and fifty-five AH. He studied under a large number of scholars and jurists, including Al-Nadr Ibn Shamil and Ashhal Ibn Hatim. A large number of scholars and jurists also studied under him, including Imam Muslim and Imam Abu Dawud, and he was praised. More than one scholar and hadith scholar, proving his trustworthiness and mastery, as the number of hadiths in the Sunan by Imam Ad-Darimi reached three Hadiths, from four paths, and the number of authentic hadiths is one hadith, as well as good hadiths, while the number of weak hadiths has reached two hadiths, but they rise to the level of good, and our last supplication is that praise be to God, Lord of the worlds, and may God Almighty’s blessings and peace be upon our master Muhammad and his family and companions and grant him abundant peace. Until the Day of Judgment.